Trade Credit and the Bank Lending Channel - Jeffrey H. Nilsen (Swiss National Bank, Study Center Gerzensee, 1999)
The bank lending channel theory posits that during monetary contractions banks restrict some firms' loans, thus reducing their desired investment independently of interest rates. Previous research finds small firms reduce, while large firms accelerate, loan growth. We find that small firms increase trade credit, a substitute credit, indicating a strong loan demand. It supports the bank lending channel: they do not voluntarily cut bank loans since they increase a less-desirable alternative. Using trade credit is propitious since unlike commercial paper (investigated by previous researchers), it is widely used by the small firms suffering the loan decline. Surprisingly, we also find large firms increase trade credit, a puzzle since they are typically assumed to have wide access to other credit. Using individual firm data, we find the reasons large firms use trade credit are financial in nature: those without a bond rating increase trade credit (i.e. without access to open market credit). As relatively few firms have this mark of quality, it implies that more firms are affected by credit constraints than previously believed.
Keywords: E44; E51; E52; E65; 330; Bank Lending Channel; Credit Channel; Manufacturing Firms; Monetary Policy; Trade Credit; Lieferantenkredit; Geldpolitische Transmission; Kredit; Firmenkundengeschäft; USA